The Implementation Effect of Employee Experience Journey, Corporate Culture Internalization, and Engagement Programs on Employee Turnover Intention in WOM Finance Company - Rofi Adiputra Darmawan; Elfrida Napitupulu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Employee Experience is defined as an organization and all of its personnel working together to build authentic and personalized work experiences so as to generate passion, innovation and productivity to strengthen individual, team and organizational performance. The population of this research is 144 employees of PT. WOM Finance Tbk, who has worked for more than 18 months, with the position of Staff and Section Head. Data analysis techniques used were validity and reliability tests, classical assumption tests, descriptive statistical tests, F tests, t tests, and coefficient of determination tests, and the data were obtained from survey results of all respondents. The results of the t test in the study stated that the Employee Experience Journey did not have a positive effect on Turnover Intention, Corporate Culture Internalization had a positive and significant effect on Turnover Intention, and the Engagement Program had a positive and significant effect on Turnover Intention.